1990
DOI: 10.1136/bmj.300.6724.566
|View full text |Cite
|
Sign up to set email alerts
|

Coffee consumption and death from coronary heart disease in middle aged Norwegian men and women.

Abstract: Objective-To study the association between number of cups of coffee consumed per day and coronary death when taking other major coronary risk factors into account.Design-Men and women attending screening and followed up for a mean of 6-4 years.Setting-Cardiovascular survey performed by ambulatory teams from the National Health Screening Service in Norway.Participants Results-At initial screening total serum cholesterol concentration, high density lipoprotein cholesterol concentration, blood pressure, height, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0
4

Year Published

1992
1992
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(64 citation statements)
references
References 8 publications
6
54
0
4
Order By: Relevance
“…The hypercholesterolemic potency of coffee diterpenes thus overrules their potential bene®cial impact on Lp(a) levels. This is evidenced by a higher rate of coronary heart disease in coffee drinkers in Norway (Tverdal et al, 1990), where boiled coffee is more common. Coffee diterpenes as such are thus unsuitable as a means of treatment for elevated Lp(a) levels, and a switch from ®ltered to un®ltered coffee is not warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The hypercholesterolemic potency of coffee diterpenes thus overrules their potential bene®cial impact on Lp(a) levels. This is evidenced by a higher rate of coronary heart disease in coffee drinkers in Norway (Tverdal et al, 1990), where boiled coffee is more common. Coffee diterpenes as such are thus unsuitable as a means of treatment for elevated Lp(a) levels, and a switch from ®ltered to un®ltered coffee is not warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Intake of diterpene-rich coffee is associated with a higher risk of heart disease (Tverdal et al, 1990), but there are also tentative indications for a protective effect against cancer. Some epidemiological studies revealed a lower incidence of colon cancer with increasing coffee intake (as reviewed by the IARC Working Group, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The association between coffee and plasma homocysteine levels was unexpectedly observed in an extensive Norwegian study (31). This association, if biologically real, may explain why coffee consumption was a predictor of coronary death in an earlier Norwegian study, even after adjusting for both smoking and serum cholesterol (19). As mentioned earlier, the John Hopkins Precursor Study, with a follow-up time of 28Á/44 years, also showed a strong doseÁ/response association between coffee consumption and CHD among non-smokers (20).…”
Section: Coffee and Diseasementioning
confidence: 92%